2013
DOI: 10.4103/0976-7800.118991
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapies for the treatment of osteoporosis

Abstract: Osteoporosis is a chronic disease of the osseous system characterized by decreased bone strength and increased fracture risk. It is due to an imbalance in the dynamic ongoing processes of bone formation and bone resorption. Currently available osteoporosis therapies like bisphosphonates, selective estrogen receptor modulators (SERMs), and denosumab are anti-resorptive agents. Parathyroid hormone analogs like teriparatide are the only anabolic agents currently approved for osteoporosis treatment. The side-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…16 Due to its anti-osteoclastogenesis effect, OPG has been studied and employed as a treatment for bone loss and osteoporosis. 3 It has been shown that the production of OPG can be stimulated in vitro by agents used against osteoporosis, such as 17β-estradiol, 3 raloxifene, 17 bisphosphonates 18 and mechanical stimuli. 19 In vivo studies also demonstrate that parenteral administration of recombinant OPG in healthy rodents results in a marked increase in bone mass and volume, and a decrease in the number and activity of osteoclasts, in addition to completely preventing bone loss induced by ovariectomy, although without adverse effects.…”
Section: Osteoprotegerin (Opg)mentioning
confidence: 99%
See 2 more Smart Citations
“…16 Due to its anti-osteoclastogenesis effect, OPG has been studied and employed as a treatment for bone loss and osteoporosis. 3 It has been shown that the production of OPG can be stimulated in vitro by agents used against osteoporosis, such as 17β-estradiol, 3 raloxifene, 17 bisphosphonates 18 and mechanical stimuli. 19 In vivo studies also demonstrate that parenteral administration of recombinant OPG in healthy rodents results in a marked increase in bone mass and volume, and a decrease in the number and activity of osteoclasts, in addition to completely preventing bone loss induced by ovariectomy, although without adverse effects.…”
Section: Osteoprotegerin (Opg)mentioning
confidence: 99%
“…2 Therefore, there is need for greater understanding of bone biology to devise new strategies and therapies to treat osteoporosis. 3 Knowledge of the molecular mechanisms involved in the bone remodeling process is of paramount importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization, patients diagnosed with OP demonstrate significantly decreased bone mineral density (BMD) compared with that of sex-matched adults (1). Osteoporotic fractures occur so frequently as to affect 1 in 3 women and 1 in 5 men over 50 years of age (2). The increasing number of osteoporotic fractures not only places a heavy economic burden on the medical care system but also leads to chronic pain, deformity, depression, disability and even death of patients.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Due to limited understandings on the underlying mechanisms, current osteoporosis therapies cannot address this imbalance properly. 7 Recent studies suggest a coordinating role of osteocytes (bone cells embedded in bone matrix) in bone metabolism by regulating activities of osteoblasts (bone formation cell) and osteoclasts (bone desorption cell), [8][9][10][11][12] which may shed new treatment strategies for osteoporosis. However, current studies of osteocytes are based on conventional cell culture, 13,14 which cannot recapitulate local in vivo microenvironments, due to its incapability to control the spatial/temporal distribution of cells and biomolecules.…”
Section: Introductionmentioning
confidence: 99%